Grade Kambing Peranakan Ettawa pada Kondisi Wilayah yang Berbeda - Nur Rasminati (Universitas Sebelas Maret (UNS), 2013)
This study aimed to determine the grade of Ettawa crossbred goats reared in lowland(coastal) areas at Wates subdistrict and highland (mountainous) areas at Pengasih subdistrict, Kulonprogo. Respondents were drawn from goat breeders who live in the village Karangwuni for lowland areas and villages Sidomulyo for highland, with the ownership of goats ranged between 2 and 20. This study used survey method, and a sample of respondents was taken by the census methods. In general, body size of goats both in lowland and highland areas were below the average standard. Some body size of goats in highland areas were higher than lowland. Based on the qualitative characteristic of the goats in lowland and highland areas were included in grade B, it has characteristics that fulfil the standards and harmonious balance, but the weight and size of the body is below the average. It can be concluded that the body sizes goat in mountain areas is higher than in the beach with a grade goat for both locations is B.Key words : Ettawa cossbred goats, grade, coastal area, mountains region